IGCSE: SPM: Add Math: Function: 01 Inverse Function

Given that f^{ -1}f (2) =(11) = 2 Given that f^{ -1}f (-1) =(2) = -1 Given that f (8) =-7f^{ -1}( ) = 8 the inverse is since Given that f^{ -1}f (11) =f^{ -1}(x) = 2x + 5 (3) = hence the inverse is since Given that f^{ -1}f^{ -1}f (9) =(x) = 2x + 5 ( ) =9 and Given that since f (-4) =-3f^{ -1}f ^{-1}f^{}(x) = ax + 5 (-3) = (-4) = -3 find a ? therefore and Given that since f (-4) =-3a( ) + 5 = -4 f^{ -1}f ^{-1}(x) = ax + 5 f^{}(-3) = -4 (-4) = -3 a= find a ? therefore and Given that since f (6) =2b( 2 ) -2 = 6 f^{ -1}f ^{-1}(x) = bx - 2 f^{}(2) = 6 (6) = 2 b= find b ? and Given that f (-5) =-1f^{ -1}g= (x) = gx - 3 find g ? and Given that f(15) =2^{ -1}f k= (x) = 5-kx find k ? find Let y= Given that therefore f(7) ^{ -1}x= f 5-2x (x) = 5-2x A. B. C. Choose the correct answer A. B. 5-y y-5 2 2 C. 5-2 y find Let y= f ^{-1}Given that so (x)= f(7) ^{ -1}f 5-2x 5-x (x) = 5-2x 2 therefore = f ^{-1}(7) find Let y= Given that therefore f(-6) ^{ -1}x= f 7x+1 (x) = 7x +1 A. B. C Choose the correct answer A. B. 1-y y-7 7 1 C. y-1 7 Given that find f(-6) ^{ -1}f(x) ^{ -1}f(-6) ^{ -1}f (x) = 7x +1 = = - Given that find f(5) ^{ -1}f(x) ^{ -1}f(5) ^{ -1}f (x) = 4x -3 = = Given that find f(5) ^{ -1}f(5) ^{ -1}f (x) = 2x -7 = Given that find f(-4) ^{ -1}gg(-4) ^{ -1}(x) = 3 -7x = Given that find g(7) g= (7) ? g(-4) ^{ -1}= 7 Given that find h(-4) ^{ -1}h(-4) ^{ -1}= h(x) = 3-2x 2 hGiven that (x) = h(-2) ^{ -1}x+1 3 find = ;x h(-2) ^{ -1}≠ -1 |

Students who took this test also took :

Created with That Quiz —
where test making and test taking are made easy for math and other subject areas.